Playing the Second World War: Call of Duty and the Telling of History - Gish, Harrison (Eludamos: Journal for Computer Game Culture, 2010)
Through its interactive representation of the Second World War, the Call of Duty series is emblematic of a contemporary form of historical remembrance. This article analyzes the ways in which the series' cut scenes and game play interrelate and represent history, warfare, and traumatic violence. Using Marita Sturken’s discussion of screen memories as sites of negotiation between differing conceptions of the past, the essay positions Call of Duty as a digital screen memory that actively produces multiple, competing understandings of historical warfare.